Efektivitas smart leadership untuk meningkatkan kepemimpinan transformasional pegawai perusahaan retail (SUKMA : Jurnal Penelitian Psikologi, 2023)
Leaders are symbols, role models, drivers and sources of influence, who can direct various activities and resources to achieve their goals. The ability to unite various human individuals formed in a group is a difficulty in itself, and one of the main tasks for a leader. The characteristics of effective leadership are leaders who can encourage their subordinates to carry out their responsibilities more than they expect, which is called transformational leadership. This research aims to measure the effectiveness of smart leadership training to improve transformational leadership in retail company employees. The research method used in this research is one group pre-test and post-test. The results of research analysis based on the Paired Sample T-Test, obtained a T value of -3.326 with a significance of 0.002 (p<0.05). This means that there is a significant difference between the transformational leadership of employees before and after being given Smart Leadership training. The results of this research can bring about changes in leadership styles that are more effective for supervisory level employees in retail companies so that they can be aligned with the company's goals.